Tuberculous Salpingitis - possible cause of salpingo-enteric fistula - Shayan Sirat Maheen Anwar, MBBS, FCPS; Anam Khan, MBBS, FCPS; Fahd Haroon, MBBS, FCPS; Farwa Mohsin, MBBS, FCPS (Radiology Case Reports, 2023)
Salpingo-enteric fistula is a rare disease causing infertility. It occurs when there is a connection between fallopian tube and the intestine. It can be accurately diagnosed with hysterosalpingography. Fistulas mostly occur as a consequence of obstetric complications, however, inflammatory bowel disease, pelvic malignancy, pelvic radiation therapy, iatrogenic causes, and trauma are other potential causes. The possibility of tuberculous salpingitis as a possible cause of salpingo-enteric fistula should always be considered in the developing countries where tuberculosis is endemic.